2022
DOI: 10.3389/fvets.2022.870904
|View full text |Cite
|
Sign up to set email alerts
|

The Global Prevalence of Neospora caninum Infection in Sheep and Goats That Had an Abortion and Aborted Fetuses: A Systematic Review and Meta-Analysis

Abstract: Neospora caninum (N. caninum) can be a potential factor causing a significant rate of miscarriages in small ruminants (sheep and goats) worldwide. Therefore, the present study aimed to determine the global status of N. caninum in sheep and goats that had an abortion and aborted fetuses. Five English databases (PubMed, ScienceDirect, Web of Science, Scopus, and ProQuest) were searched for relevant scientific articles published from their inception until November 4, 2021. Finally, 21 studies conducted on sheep (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 76 publications
2
15
1
Order By: Relevance
“…The global prevalence of N. caninum in aborted fetuses of sheep and goats using molecular methods was reported to be 7-15% [31]. While the prevalence in our study was 14.8% and 11.8% in sheep and goat, respectively.…”
Section: Discussioncontrasting
confidence: 64%
“…The global prevalence of N. caninum in aborted fetuses of sheep and goats using molecular methods was reported to be 7-15% [31]. While the prevalence in our study was 14.8% and 11.8% in sheep and goat, respectively.…”
Section: Discussioncontrasting
confidence: 64%
“…N. caninum is considered as a major cause of abortion in cattle, particularly in dairy cattle, and studies revealed that 12% to 42% of aborted fetuses from dairy cattle were infected with N. caninum (1). Furthermore, goats would abort infectious fetuses when they were inoculated with N. caninum during pregnancy, and a meta-analysis revealed that the prevalence of N. caninum in aborted fetuses of goats was 7% worldwide (10,11). Its zoonotic potential remains unknown because no evidence indicates that humans have been infected with N. caninum successfully (12,13).…”
Section: Introductionmentioning
confidence: 99%
“…Similar to T. gondii, N. caninum has also been widely concerned and studied since it was first reported in 1984 ( 9 ). N. caninum can be transmitted horizontally and vertically in herds ( 10 ). N. caninum is considered as a major cause of abortion in cattle, particularly in dairy cattle, and studies revealed that 12% to 42% of aborted fetuses from dairy cattle were infected with N. caninum ( 1 ).…”
Section: Introductionmentioning
confidence: 99%
“…Due to the high frequency of domestic dogs (95.8%), the odds ratio could not be determined. Canids are the final hosts of N. caninum , so their presence would be expected to be a risk factor for goats [ 30 , 41 ]. Thus, this variable should not be ruled out as a risk factor for N. caninum .…”
Section: Discussionmentioning
confidence: 99%